2021
DOI: 10.1002/jcaf.22497
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary disclosure volume: Evidence from acquiring firm's press releases during M&A

Abstract: This study examines the determinants and effects of firms’ merger and acquisition voluntary disclosure. It focuses on the press releases disclosed by acquiring firms during the transaction period. The findings suggest that management provides more news updates for stock financed transactions compared to those without stock finance. Larger deals with more economic significance tend to disclose more news during the transaction period. The news update volume during the transaction period is positively related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Research on factors affecting the quality of corporate disclosure has found that effective internal governance and external supervision, virtuous product market competition, developed financial market, favorable legal environment, and the speed of government intervention can significantly improve the quality of disclosure of listed companies [3][4][5]. At the same time, there is a governance effect of short selling on management discussion and analysis of disclosure [6]. Therefore, the deterrence of short selling will standardize management's strategic disclosure behavior and further improve the transparency of corporate information.…”
Section: Introductionmentioning
confidence: 99%
“…Research on factors affecting the quality of corporate disclosure has found that effective internal governance and external supervision, virtuous product market competition, developed financial market, favorable legal environment, and the speed of government intervention can significantly improve the quality of disclosure of listed companies [3][4][5]. At the same time, there is a governance effect of short selling on management discussion and analysis of disclosure [6]. Therefore, the deterrence of short selling will standardize management's strategic disclosure behavior and further improve the transparency of corporate information.…”
Section: Introductionmentioning
confidence: 99%